THE ESSENCE OF DIGITIZATION OF THE FINANCIAL SYSTEM AND ITS SIGNS - MYKHALCHUK, Bohdan (Scientific journal «World of Finance», 2026)
Вступ. Цифровізація фінансової системи є ключовим чинником модернізації економіки та підвищення її ефективності. Вона охоплює впровадження цифрових технологій у банківську, платіжну й інвестиційну сфери, сприяючи прозорості, швидкості та доступності фінансових послуг. Цифровізація фінансової системи забезпечує більш інклюзивне, прозоре та ефективне фінансове середовище. На сьогодні в науковій літературі нема єдиного підходу до розуміння економічного змісту цього поняття. Тому дослідження сутності цифровізації фінансової системи та з’ясування її основних ознак набуває актуальності. Мета – дослідити сутність цифровізації фінансової системи та виокремити іманентні властивості, що притаманні цьому процесу. Результати. Досліджено підходи до економічного змісту поняття цифровізації та запропоновано авторське бачення сутності цифровізації фінансової системи. Виокремлено іманентні властивості, що притаманні процесу цифровізації фінансової системи. Висновки. Цифровізація фінансової системи виступає каталізатором економічного розвитку: модернізує фінансову інфраструктуру та стимулює інновації. Це складний багатогранний процес, що передбачає створення нових і вдосконалення діючих інформаційно-комунікаційних й ІТ-технологій та впровадження їх в діяльність фінансових агентів на всіх рівнях фінансових відносин з метою розширення доступності надаваних фінансових послуг, підвищення їхньої якості та ефективності фінансового менеджменту, що сприяє формуванню нової моделі фінансової системи, пришвидшенню соціально-економічного розвитку держави. Introduction. The article reveals the essence of the process of digitalization of the financial system as a multifaceted phenomenon that covers all areas of financial relations and is based on the implementation of modern information and communication technologies. It is shown that digitalization is not only a tool for technological renewal, but also a key factor in increasing the efficiency of the functioning of financial institutions, forming a competitive environment, ensuring transparency and inclusiveness of financial services. Scientific approaches to interpreting the concept of “digitalization” are analyzed, the main areas of its impact on the financial system and the features of its manifestation in modern conditions of economic transformation are identified. It is substantiated that digitalization acts as a catalyst for economic growth, contributes to the innovation of financial activities, expanding the capabilities of financial markets and increasing the level of financial inclusion of the population. The paper identifies key features of the digitalization of the financial system: innovation, comprehensiveness, financial inclusion, technical and technological, virtualization and transparency of the financial space, as well as effective verification of digital data. It is emphasized that the introduction of digital technologies transforms financial flow management models, improves the quality of financial management, reduces transaction costs and provides operational access to financial services for all market participants. The purpose of the article is research into the essence of digitalization of the financial system and identification of the inherent properties inherent in this process. Results. The approaches to the economic content of the concept of digitalization are investigated and the author’s vision of the essence of the digitalization of the financial system is proposed. We will highlight the immanent properties inherent in the process of digitalization of the financial system. Conclusions. Digitalization of the financial system acts as a catalyst for economic development: it modernizes the financial infrastructure and stimulates innovation. Digitalization of the financial system is a complex multifaceted process that involves the creation of new and improvement of existing information and communication and IT technologies and their implementation in the activities of financial agents at all levels of financial relations in order to expand the availability of financial services provided, improve their quality and the efficiency of financial management, which contributes to the formation of a new model of the financial system and accelerate the socio-economic development of the state.